STRATEGI PEMASARAN DESTINASI WISATA AIR PANAS WATERBOOM SULILI KABUPATEN PINRANG DI MASA COVID 19 - Suardi Suardi (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2021)
This study aims: to explained the marketing strategy by manager of hot water tourism Sulili Waterboom Pinrang Regency to development of tourism destination potency in Covid 19 Era, and to implementation the marketing strategy by manager of hot water tourism Sulili Waterboom Pinrang Regency to development of tourism destination potency in Covid 19 Era. The analytical method used: the quantitative and qualitative method which source from primary and secondary data. The technique of data gathered include interview, observation, library research and documentation. Data obtained it to arrangement and preparation and analysis with used of qualitative descriptive such as the explained then to analysis and naration. The results of this study indicate: the manager of hot water tourism Sulili Waterboom Pinrang Regency applied of marketing strategy STP as the important strategy to increasingthe local and national tourism visiting come to Pinrang Regency for holiday and recreation which have contribution to increased the regional income. The pandemic Covid 19 era the total tourism visiting to decreasing, cause it require to applied of seriously attempt from management parties to commitment applied of marketing strategy STP which reorientation to increased the segmentation of local or national tourist, with marketing target for general visitor from all of ages and to become the positition of Waterboom Tourism Destination as the main of tourism visiting in Pinrang Regency.